2D electrical resistivity tomography (ERT) investigation of a landslide: A case study from Ali Mendjeli, Constantine, North-East of Algeria. Issue 1 (31st December 2023) - Chibani, Ammar; Hebbache, Kamel; Mellas, Mekki; Mabrouki, Abdelhak
ABSTRACT: Constantine is city characterised by a very rugged relief in which frequently happened the collapse of buildings as a result of landslide hazards. The aims of this study are to determine the depth of the surface landslide and to evaluate the landslide mass in the new city of Ali Mendjeli, which is nearby Constantine in Northeastern Algeria, using a geophysical method, namely the electrical resistivity tomography (ERT). Five two-dimensional (2D) ERT profiles were performed along and across the landslide using Wenner electrode array. Two parallel profiles to the sliding direction of 69 m length of each profile and three other perpendicular profiles, each with a length of 115 m, were conducted with inter-electrode spacing of 3 and 5 m, respectively. The resistivity data processing was carried out using Res2Dinv software. The inverted pseudo-section models presented formations characterised by low resistivities which can be summarised in two sets ranging from 1.38 to 6.20 Ωm and from 6.20 to 19 Ωm. The inverted resistivity data were correlated and calibrated with respect to the subsoil lithology obtained by well drilling and inclinometer tests. According to the inclinometer displacements, the measurements were of the order of 2–3 mm for a depth of 10 m and between 17.5 and 19.5 m for a depth of 13 m. The combined measurements of ERT and the geotechnical testing not only have shown a good agreement in the results obtained but also have successfully detected the depth of probable rupture surfaces and displaced materials likely to slip. This concordance of the obtained results. The estimated volume of the sliding material was around 20.000 m 3 . According to the obtained results of this study, ERT can be applied to detect sliding surfaces in landslides.